2021
DOI: 10.1007/s13300-021-01097-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of and Preferences Between Characteristics of Injectable Diabetes Treatments

Abstract: Introduction: The administration of medications targeting type 2 diabetes mellitus (T2D) has evolved over time. As injection delivery systems continue to evolve, it is necessary to understand patients' perceptions of currently available treatments. The objective of this study was to examine the patient perspective of injectable treatment for T2D and identify characteristics of these treatments that are most important to patients.Methods: Data were collected via an online survey study with a sample of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
3
15
0
1
Order By: Relevance
“…39 Results of a survey of 504 people with type 2 diabetes in the United States or the United Kingdom identified confidence in administering the correct dose (59.5% of participants), ease of selecting the correct dose (53.2% of participants), overall ease of use (47.4% of participants), and frequency of injections (44.2% of participants) as the most important features that would determine their choice of an injection device (selected from 17 attributes). 43 These results confirmed previous reports indicating that receiving the correct insulin dose is the primary concern of individuals using insulin pen injectors 46,47 and that the likelihood of people using a device increases with their perception of its ease of use. 45,48,49…”
Section: Factors Affecting the Performance Of Insulin Pen Injector Te...supporting
confidence: 89%
“…39 Results of a survey of 504 people with type 2 diabetes in the United States or the United Kingdom identified confidence in administering the correct dose (59.5% of participants), ease of selecting the correct dose (53.2% of participants), overall ease of use (47.4% of participants), and frequency of injections (44.2% of participants) as the most important features that would determine their choice of an injection device (selected from 17 attributes). 43 These results confirmed previous reports indicating that receiving the correct insulin dose is the primary concern of individuals using insulin pen injectors 46,47 and that the likelihood of people using a device increases with their perception of its ease of use. 45,48,49…”
Section: Factors Affecting the Performance Of Insulin Pen Injector Te...supporting
confidence: 89%
“…The first insulin injections were made with large and heavy glass or metal syringes and reusable needles (4,7,(24)(25)(26). Syringe was the only possible way of delivering insulin in clinical practice for the next several decades (4,7,27).…”
Section: First-generation Insulin Pensmentioning
confidence: 99%
“…American and European guidelines underline the necessity of undertaking patient preference when selecting diabetes treatment especially when treatment is accoutered with pain due to injection ( 24 ). That is why recently a study assessing the patient perspective of injectable treatment among patients with type 2 diabetes (T2DM) has been performed and showed that there are some features of the injection device that patients choose more often which may help in future improvement of insulin pens ( 25 ). Development of insulin pens is parallel to the development of newer insulin formulation where insulin pen must adapt to changes to dosing and timing requirements like it is in case of modern ultra-long-acting insulin analogue icodec, administered once weekly, which is under development ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…End users of all educational levels should be represented, and their involvement should continue throughout the development process, including the testing of early prototypes and new products with providers. Once products have reached the market, post-marketing surveillance and other types of user data, such as patients’ perceptions and preferences, 2 offer insights from their real-world use that can be used by developers to improve the next product versions or generations.…”
Section: Human-centered Design To Serve People Living With Diabetes: ...mentioning
confidence: 99%